IMPACTS OF INDUSTRIAL PAINTINGS ON WORKERS’ HEALTH - Karine Cordeiro Santos, Cristiane; Cristina Condé, Renata; Ferreira da Silva Junior, Rene; Lohany Cordeiro Souto, Brenda; Maria Cordeiro Cardoso, Julia; Cristiane Soledade Dias, Kátia; Vieira da Silva, Cristiane; Jose Afonso Goncalves Araujo, Matheus; Nayara Pereira Jatobá, Jéssica; de Pinho Amaral, Bruno; Carlos Pereira de Jesus, Ely; de Andrade Costa, Amanda; et al. (Health and Society, 2023)
Objective: to describe the impacts of industrial paintings on workers’ health. Methods: an integrative literature review study was conducted. Articles recovered through secondary databases Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (Scielo) and Online Medical Literature Search and Analysis System (MEDLINE) were analyzed from the descriptors paintings, worker’s health and occupational medicine. Studies published in Portuguese, English or Spanish were considered and dealt directly with the theme object of study. Results: the main impacts of industrial paintings on workers’ health are skin diseases, allergic reactions, eye irritation and respiratory problems, neoplasms, myelodysplastic syndromes, neuropathies, olfactory disorders, saturnism and acute and chronic effects on the central nervous system. Conclusion: industrial paintings can cause real risks to the health of workers in this service sector, which requires the performance of occupational health professionals for timely prevention and care.